Self and Philosophy in the Gnostic Novel - Abdulrazzaq Ali Hussien , Researcher. Tuqa; Abdulhussien Khalaf, Prof. Dr. Aqeel (Basra studies journal, 2026)
This study aims at exploring the various techniques of self-revelation in Iraqi narrative, through the fabric of philosophy, which occupies a significant space in the ‘irfāni (gnostic) novel. Philosophy is employed in multiple forms, grounded in the scientific field that contributes to shaping the complete image of narrative construction. The novel presents itself as a stage for philosophical expression through narrative techniques such as dialogue—both pure and monologic—using two key devices: genre blending and intertextuality. These tools help articulate the ideology of the intended self within this philosophical structure, which in turn evokes the reader’s mind to easily identify a specific form of the lost self: the scientific self. This self emerges with greater collective reassurance and a smoother reliance on the Islamic philosophical heritage.